Embedding religious character education through Karawitan in children - Sriana; Saiful Anwar (Journal of diversity in learning (JDIL), 2023)
Religious character education prioritizes character building in children without neglecting the child's formal education. Elementary schools develop and nurture Karawitan to know how to instil and the impact of cultivating a religious character through the Karawitan itself. The type of research used in this study used a qualitative field study at SDN 4 Krebet, Jambon, Ponorogo. Data collection techniques using documentation, interviews, and observation. Data analysis uses data presentation, conclusion verification, and data reduction. In addition, data validity is carried out by extension, increasing accuracy in the research, extending observations, and triangulation. The cultivation of religious character at SDN 4 Krebet Jambon is instilled through songs (gendhing) or songs, wearing closed uniforms when playing karawitan, conveying material (history of musical instruments and vocals) from the walisongo era, and getting used to the krama language when playing karawitan. From cultivating the Karawitan above, students become accustomed to singing Islamic songs with all their hearts, wearing closed or Muslim clothing, knowing the history of various musical instruments and vocals in Karawitan and are accustomed to speaking krama when conversing in everyday life. The religious character through this Karawitan is inspired by the struggles of the walisongo who spread the Islamic religion through the skills of the land of Java, which are popular with the community. Besides being able to shape the religious character of students, Karawitan can also foster a sense of love for culture and love for the motherland.